The Relationship between Parenting Style and Nutrition Status of Child Aged 12-24 Months at Jelbuk Public Health Center, Jember Regency - Winarsih , Sri; Fatkuriyah, Lailil; Widada, Wahyudi; Nafista, Ulfia Fitriani (LPPM Universitas dr. Soebandi, 2024)
Children aged 12-24 months are included in the golden period of the first 1000 days of life, wheretheir nutritional needs greatly affect growth and development in the future. The role of themother is very influential in the upbringing and care of the child. This study aimed to determinethe relationship between parenting style and nutritional status of babies aged 12-24 months atthe Jelbuk Public Health Center, Jember Regency. The research design used was cross-sectional.The sampling technique used proportionate random sampling and obtained a total sample of 97mothers and babies under two years. Mothers were instructed to fill out mother's parentingquestionnaires. The nutritional status of children under two years is measured by weight/ageindicators and interpreted based on the WHO classification of nutritional status. The child'sweight was obtained using a hanging-type scale (dacin). Statistical analysis using Spearman rankwith significance ≤0.05. Most children (50%) of mothers with permissive parenting areunderweight, 47.1% are normal, and 2.9% are at risk of being overweight. Most children (86%)of mothers with democratic parenting have normal nutritional status, and 14% are underweight.Most children (83.3%) of mothers with authoritarian parenting have normal weight, and 16.7%are underweight. There is a relationship between parenting style and the nutritional status ofchildren aged 12-24 months (p value = 0.001; α = 0.05). The application of democratic parentinghas the potential to cause normal weight in children. Therefore, health promotion is neededabout parenting by related parties to mothers of children because parenting affects eating habitsthat impact children's nutritional status.